ASSOCIATION BETWEEN MALAT1 RS4102217-POLYMORPHIC VARIANT AND ISHEMIC ATHEROTHROMBOTIC STROKE DEVELOPMENT IN PEOPLE WITH INCREASED BODY MASS INDEX - Karina A. Moiseіenko; Victoriia Yu. Harbuzova; Olha A. Obukhova (Eastern Ukrainian Medical Journal, 2022)
Background. The recent discovery of a group of mediators known as long non-coding RNAs (lncRNAs) is the basis for research that will reduce the risk of cardiovascular disease in the long run. lncRNAs are expressed depending on conditions, and there is ample evidence of their involvement in a variety of biological processes. Indeed, lncRNA abnormalities are directly related to human diseases, including cardiovascular pathology and other diseases. LncRNA MALAT1 is one of the numerous factors causing functional changes in ischemic atherothrombotic stroke (IATS), in particular, it affects the functioning of endothelial cells and is involved in the implementation of inflammatory processes and regulation of autophagy. All those conditions play a role in the development of atherosclerosis, which underlies the pathogenesis of IATS. The effects of rs4102217-polimorphism of MALAT1 on IATS were poorly explored. This research aimed to find out, whether MALAT1 was associated with the susceptibility to IATS in patients with overweight. Materials and Methods. A total of 200 ischemic atherothrombotic stroke patients and 234 controls without acute cardiovascular pathology were enrolled in this study. The rs4102217-polymorphisms in the promoter of MALAT1 were genotyped by using Real-Time PCR. Calculations were made using Statistical Package for the Social Sciences software (SPSS, version 17.0). A value of P ˂ 0.05 was considered as statistically significant. Results. The SNP rs4102217 in the promoter of MALAT1 was associated with the risk of ischemic atherothrombotic stroke in people with increased body mass index (BMI ≥ 25 kg/m2) (Dominant model: adjusted OR = 1.66, 95% CI, 1,024–2,700, P = 0.040) Conclusions. The results showed that c-carriers with elevated BMI were 1.66 times more likely to develop ischemic atherothrombotic stroke.